(3GddWGFa aj GdMcGjGJs - (3GHf GdOHjKj , eMeO Hf SYjO Hf jMji, CHh YHO Gddg GdYQGbj,J (B637 (3g` s
(3ChdgG (B:s
(3oMcj Yf CHj SdjeGf GdOGQGfj Cfg bGd(B: (3GNJdaJ Edi eLdS bGV aCKQ cdGeg aj bdHj s
(3BNQgG (B:s
(3jbhdhf GdReGf Hg aSGO hge aSOhG heG aSO GdReGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3hJJVef aj OGNdgGs
"(3eG jQhi Yf GdLGMX eFI cdeI dYdj Hf CHj WGdH(B"s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B139 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B40s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B167 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs